Are ultrasound renal aspects associated with urinary biochemistry in fetuses with lower urinary tract obstruction?1. (1st December 2016) - Nassr, Ahmed A.; Koh, Chester Koh; Shamshirsaz, Alireza A.; Espinoza, Jimmy; Sangi‐Haghpeykar, Haleh; Sharhan, Dina; Welty, Stephen; Angelo, Joseph; Roth, David; Belfort, Michael A.; Braun, Michael; Ruano, Rodrigo
Abstract: Objective: To evaluate the association between ultrasonographic renal parameters and urine biochemistry in fetuses with lower urinary tract obstruction (LUTO). Methods: Data were collected prospectively from 31 consecutive fetuses with LUTO that underwent vesicocentesis for fetal urinary biochemistry between April 2013 and September 2015. The following renal ultrasound markers were assessed immediately before the vesicocentesis: renal echogenicity, presence of cortical cysts, presence of findings suggestive of 'renal dysplasia' (hyperechogenic cystic kidneys with no cortical‐medullary differentiation) and severe oligohydramnios (amniotic fluid < 5th percentile). The association of these parameters to the fetal urinary concentration of sodium, chloride, calcium, osmolality and beta2‐microglobulin was investigated by logistic regression analysis. Results: There was no relationship between any of the ultrasonographic fetal renal characteristics and fetal urinary biochemistry. Conclusions: In LUTO, the ultrasound appearance of the fetal kidneys and urinary biochemistry are not correlated. It may be better to take both ultrasound and biochemistry into account when evaluating fetuses with fetal LUTO. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? In fetal lower urinary tract obstruction (LUTO), prenatal renal function is evaluated by fetal urinary biochemistry and renal ultrasound What does this study add? In LUTO, fetal renal ultrasound and urinary biochemistry are not associated The combination of renal ultrasound characteristics and biochemistry should be taken into account